Exploring the Formation of Relational Collaboration among Competitors - Nur Alamzah; Badri Munir Sukoco; Indrianawati Usman (Universitas Airlangga, 2022)
Objective: This paper aims to explore how a relational collaboration process is formed among bag and suitcase craftsmen in an Industrial Village in Indonesia. Design/Methods/Approach: The study is a qualitative case study formulated from nine informants interviewed with different roles, from the initiators, actors, and community leaders to local government agencies. Information collected is analyzed using the Gioia method with the three stages of analysis: concepts, themes, and dimensions. Findings: Different from previous research, which stated that three perspectives of the interaction form of the dynamics of business competition, namely rivalry, competitive-cooperation, and relational, can only be manifested mutual-exclusively according to a certain cultural context, this study finds that those perspectives can be manifested as an evolutionary stage. which we label as